2016
DOI: 10.1080/23744235.2016.1185534
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophiliaventilator-associated pneumonia. A retrospective matched case-control study

Abstract: Stenotrophomonas maltophilia is a possible, yet infrequent cause of VAP. No outcome differences were found when compared to matched VAP caused by other Gram-negative bacilli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The present study echoes their findings, indicating that hematological abnormalities complicate the clinical course of SM respiratory infection and worsen the disease outcome. Although neutrophil counts may have been a decisive factor in infection control and hematopoiesis ability, it was also shown to be a significant risk factor in PH in previous studies ( 18 ). After multivariate analysis, we found that neutropenia was not an independent risk factor in PH or associated mortality, implying that neutropenia is, probably, a collateral finding along with underlying disease and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 93%
“…The present study echoes their findings, indicating that hematological abnormalities complicate the clinical course of SM respiratory infection and worsen the disease outcome. Although neutrophil counts may have been a decisive factor in infection control and hematopoiesis ability, it was also shown to be a significant risk factor in PH in previous studies ( 18 ). After multivariate analysis, we found that neutropenia was not an independent risk factor in PH or associated mortality, implying that neutropenia is, probably, a collateral finding along with underlying disease and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, 1,156 papers were initially searched in the database through the search strategy, and then 43 papers were selected through title, abstract and keywords, etc. Finally, eight papers ( 9 16 ) were further screened by reading the full text, including five papers in English and three papers in Chinese ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regimes based on the use of CZA have been already demonstrated to be more effective than other available antibiotic agents for the treatment of infection caused by class A carbapenemase (KPC) producing K. pneumoniae [ 25 ] in critically ill mechanically ventilated patients [ 26 ]. However, few data are available concerning its efficacy in the treatment of DTT non-fermenter gram-negative (NFGN) bacteria such as Pseudomonas spp., Burkholderia cepacia , and Stenotrophomonas maltophilia which are frequently associated with VAP [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%